Residues thinking through chemical environments - Boudia, Soraya; Creager, Angela N. H. 1963-; Frickel, Scott 1965-; Henry, Emmanuel 1969-; Jas, Nathalie; Reinhardt, Carsten 1966-; Roberts, Jody A. 1976- (Rutgers University Press, 2022)
Residues properties -- Legacy -- Accretion -- Apprehension -- Residual materialism.
Literaturverzeichnis Seite 145-169. - Index
Keywords: Herstellung; Rückstand; Chemische Industrie; Schadstoff; Umweltschaden; Chemikalie; Chemical industry / Environmental aspects; Pollution; Chemistry, Technical / Environmental aspects; Chemistry, Technical / Social aspects; Chemicals / Safety measures; Environmental policy; Environmental sociology